Violence, prophétie et apothéose dans les Fastes d’Ovide : d’Ino à Mater Matuta (VI, 475-550) - Justine Kaleta (Cahiers des Études Anciennes)
The story of Ino is filled with violence, which she both perpetrates and falls victim to. It however ends with a divinization to which Ovid gives an unprecedented twist. He adds to the narrative an episode of violence on Italian soil, where Juno’s cunning speech prompts Latin maenads to attack Ino and her son, until they are saved by Hercules and taken in by the nymph Carmentis, who prophesies their transformation. The Latin poet thus replaces the abrupt apotheosis of the Greek narratives with a sequence that highlights the role of words and hospitality in inciting as well as solving violence. In response to Juno’s speech designating Ino as a stranger to the land and the rites of Latium, the prophetic voice of Carmentis seals the proximity of the future Mater Matuta and her son to Italy and to the Rome to come – a pacifying role here analyzed in detail.